(untitled) (Al-Academy, 2025)
This research aims to explore the feasibility of designing a proposed mobile exhibition to raise awareness of the legacy of surrealist art. To achieve this, a descriptive-analytical approach was used by examining the traveling exhibition and surrealist art. The experimental approach is also followed within the applied framework of the research through designing a proposed mobile exhibition to raise awareness of the legacy of surrealist art. A purposive sample of six surrealist artworks was selected, digitally copied from the original painting. These works were selected based on their relevance and suitability to the current research topic, as well as their diversity in artistic forms. The research results demonstrated the potential of mobile exhibitions to present artistic information in an engaging and engaging manner, consistent with the nature of surrealist art, which relies on mystery and visual excitement. Surrealist art also utilizes unconventional and innovative display methods to ensure its message and concept reach the largest possible audience. The mobile exhibition’s ability to showcase the aesthetics of surrealist art in a more engaging and in-depth manner contributes effectively to communicating the unfamiliar surrealist concept. The research recommends studying the scalability and applicability of mobile exhibition design to include various contemporary art movements. Field studies should also be conducted to measure the actual cognitive and cultural impact of the mobile exhibition after its implementation in the target communities. It also recommends enhancing cooperation between cultural, artistic, and educational institutions to organize joint mobile exhibitions that contribute to consolidating awareness of art history and its development. It also recommends educating the public about the legacy of surrealist art through multiple lectures and workshops, thus affirming its importance as an influential modern art form